2020
DOI: 10.2215/cjn.11951019
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Jurisdictional Scan of the Evidence Characterizing and Evaluating Assisted Peritoneal Dialysis Models

Abstract: Background and objectivesCompared with hemodialysis, home peritoneal dialysis alleviates the burden of travel, facilitates independence, and is less costly. Physical, cognitive, or psychosocial factors may preclude peritoneal dialysis in otherwise eligible patients. Assisted peritoneal dialysis, where trained personnel assist with home peritoneal dialysis, may be an option, but the optimal model is unknown. The objective of this work is to characterize existing assisted peritoneal dialysis models and synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(132 reference statements)
0
24
0
2
Order By: Relevance
“…Payment to the medical staff assisting with PD in the home could not come directly from the dialysis organization or healthcare provider, as this could be construed as an “inducement” and would violate the Stark Law. New processes and regulatory endorsement for payment are necessary to increase enthusiasm to apply this as an approach to increase home access 22 . For many ESKD patients, particularly elderly patients in the COVID era, assisted PD may be more optimal than in‐center HD, potentially reducing exposure risk for infection in transit or within the clinic itself.…”
Section: Novel Models Of Carementioning
confidence: 99%
“…Payment to the medical staff assisting with PD in the home could not come directly from the dialysis organization or healthcare provider, as this could be construed as an “inducement” and would violate the Stark Law. New processes and regulatory endorsement for payment are necessary to increase enthusiasm to apply this as an approach to increase home access 22 . For many ESKD patients, particularly elderly patients in the COVID era, assisted PD may be more optimal than in‐center HD, potentially reducing exposure risk for infection in transit or within the clinic itself.…”
Section: Novel Models Of Carementioning
confidence: 99%
“…Direct visualization of the peritoneum and placement of PD catheter by advanced laparoscopy has been very successful in most instances [34,35]. Frailty, advanced age, poor vision, psychiatric or memory issues and lack of motor skills are not contraindications to PD but mere barriers that can be overcome with assisted PD, either provided by the family members at home or by trained personnel at home or nursing facilities [36][37][38][39][40]. Assisted PD programs have been successful in other countries such as Canada, Denmark, and France [38,[41][42][43].…”
Section: Patients Selectionmentioning
confidence: 99%
“…As a feasible option for patients who cannot perform their own PD exchanges, assisted PD have been developed in many countries with the aim of overcoming barriers in older and nonself-su cient patients, and some studies suggested that the use of assisted PD could increase the utilization of PD patients among older [12][13][14] . However, whether assisted PD achieved similar outcomes to self-care peritoneal dialysis still remained controversial 15 . Therefore, we conducted the present study to investigate the outcomes of assisted PD in ageing patients, by comparing patients undergoing assisted PD with those on self-care PD in a cohort of older patients.…”
Section: Introductionmentioning
confidence: 99%